Supporting Irrational Suicide - Hardcastle, Valerie Gray (Bioethics, 2002)
In this essay, we present three case studies which suggest that sometimes we are better off supporting a so–called irrational suicide, and that emotional or psychological distress – even if medically controllable – might justify a suicide. We underscore how complicated these decisions are and how murky a physician's moral role can be. We advocate a more individualized route to end–of–life care, eschewing well–meaning, principled, generalizations in favor of a highly contextualized, patient–centered, approach. We conclude that our Western traditions of promoting reasoned behavior and life themselves may at times be counter–productive.